The tyrosine phosphatase CD148 is excluded from the immunologic synapse and down-regulates prolonged T cell signaling - Lin, Joseph (The Rockefeller University Press, 2003)
CD148 is a receptor-like protein tyrosine phosphatase up-regulated on T cells after T cell receptor (TCR) stimulation. To examine the physiologic role of CD148 in TCR signaling, we used an inducible CD148-expressing Jurkat T cell clone. Expression of CD148 inhibits NFAT (nuclear factor of activated T cells) activation induced by soluble anti-TCR antibody, but not by antigen-presenting cells (APCs) loaded with staphylococcal enterotoxin superantigen (SAg) or immobilized anti-TCR antibody. Immunofluorescence microscopy revealed that the extracellular domain of CD148 mediates its exclusion from the immunologic synapse, sequestering it from potential substrates. Targeting of the CD148 phosphatase domain to the immunologic synapse potently inhibited NFAT activation by all means of triggering through the TCR. These data lead us to propose a model where CD148 function is regulated in part by exclusion from substrates in the immunologic synapse. Upon T cell–APC disengagement, CD148 can then access and dephosphorylate substrates to down-regulate prolongation of signaling.